2007
DOI: 10.1049/el:20071226
|View full text |Cite
|
Sign up to set email alerts
|

Blue lasing at room temperature in an optically pumped lattice-matched AlInN/GaN VCSEL structure

Abstract: Laser action with low threshold average pump power density ( $ 50 W Á cm À2 ) at room temperature is reported for a crack-free planar vertical cavity surface emitting laser (VCSEL) structure based on a bottom lattice-matched AlInN=GaN distributed Bragg reflector (DBR) and a top dielectric DBR. The cavity region, formed by n-and p-type GaN layers surrounding only three InGaN=GaN quantum wells, corresponds to a typical active region suitable for an electrically driven VCSEL. In addition to low threshold, a spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…To complete our analysis, we also studied the evolution of the RT lasing threshold power density P thr measured on an InGaN/GaN MQW vertical cavity surface emitting laser (VCSEL) similar to that of Ref. [33] using the abovementioned nonresonant excitation scheme as a function of δ (Fig. 6(a)).…”
Section: Invitedmentioning
confidence: 99%
“…To complete our analysis, we also studied the evolution of the RT lasing threshold power density P thr measured on an InGaN/GaN MQW vertical cavity surface emitting laser (VCSEL) similar to that of Ref. [33] using the abovementioned nonresonant excitation scheme as a function of δ (Fig. 6(a)).…”
Section: Invitedmentioning
confidence: 99%
“…2) These two features make Al x In 1Àx N an ideal material for a high quality Al x In 1Àx N/GaN distributed Bragg reflector for visible and near ultraviolet optoelectronics. 3,4) The spontaneous large polarization difference with respect to GaN also gives rise to the high sheet charge density two dimensional electron gas (2DEG) at the Al x In 1Àx N/GaN interface without strain-induced polarization. The absence of the latticemismatch related stress improves the structural stability and thus the reliability of the electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…As far as optically pumped GaN-based VCSELs are concerned, there are only few experimental results in recent years [22]- [25]. In our previous study, we also demonstrated optically pumped GaN-based VCSELs by employing dielectric DBR VCSEL [26], [27] and hybrid DBR VCSEL structures [28], [29].…”
Section: Introductionmentioning
confidence: 99%